Thermal treatment of soils contaminated with gas oil: Influence of soil composition and treatment temperature - Piña, Juliana (2002)
Samples of two soils containing different organic matter contents, neat or contaminated with gas oil (diesel fuel oil) at 2.5wt.% were heated from room temperature to different final temperatures (200-900°C). The experiments, performed in an anaerobic media, simulate conditions pertinent to ex situ thermal desorptive and thermal destructive treatments. The products generated during the heating were collected and light gases were analyzed by gas chromatography. The results indicate that the chemical composition of the soil is a key factor since it strongly influences the quantity and composition of the off-gases. According to the liquid and light gas yields, the gas oil does not affect appreciably the generation of pyrolysis products of the own soil constituents and the gas oil does not suffer significant chemical transformations even at high operating temperatures (e.g. 900°C). With surface areas of 16000cm2/g (Soil A) and 85000cm2/g (Soil B) based on the monolayer adsorbed model, 4 and 20%, respectively, of the original gas oil can be adsorbed. These values are in good agreement with experimental data. Even for high temperatures, the employed thermal treatment is capable to practically remove the gas oil from the soil bed without changing appreciably the original chemical composition of the contaminant.